JENIS POHON, PEMANFAATAN SERTA KEPERCAYAAN MASYARAKAT DESA PELIATAN, KECAMATAN UBUD, GIANYAR-BALI - Suarna, I W.; G. R. Dalem, A. A.; Wirasiti, N. N. (Bumi Lestari; Vol 6 No 1)
A study on identification of trees species, their use as well as what the community believe about them held in Peliatan Village, Ubud District, Gianyar Regency (Bali) on February, 2005. The study was carried out by taking a walk along the roads or trails which were assessed for their potentials as tracking trails in this village while taking notes on the tree species observed. The trees then were determined their status, their use as well as what the community believe about them. Results of this study show that there were 148 kinds of trees which have been identified on this village. From the use perspective, it was revealed that these trees could give a wide range of benefits for the community of Peliatan as well as Bali in general. Their use for decorations, provides shady spots, as well as uncultivated trees were the highest in their proportion (22%). In addition, in this village they were also identified 18% of trees which believed to provide a possitive or negative impacts to humans. Most of them (73%) were believed to be related to positive impacts to humans.
Keywords: trees, use, believe, Peliatan Village